Maximising happiness at work : are we in the right industry that best suits our personalities and what maximises happiness at work? - Ng, Jia Yi. (2012)
This paper aims to achieve two objectives: Firstly, to assess if individuals are in the industry that best fits their BIG Five Personality Traits , and secondly to examine the overall influence of Big Five Traits, industry type, and the interaction of Traits on Industry via a Match Variable on Job Satisfaction. On the first objective, we will look for the BIG Five Traits that increase the likelihood of being in each industry using a Multinomial Regression (Model 1). Next we will assess the actual traits that increase Job Satisfaction in each industry using Ordinary Least Square method (Model 2). A cross analysis between these two models allows us to observe if there are matches between traits that increase the chance to be in a particular industry and traits would enhance Job Satisfaction for that industry. To further probe into the question if individuals are in the industry that best fit them, we introduce the Match Variable to evaluate the extent of fit between the actual industry one is currently in and the supposedly “Best Fit Industry” for each respondent in the third model. As add-ons to previous research, we investigate this topic using industrial type rather than occupational type to thoroughly analyze the unique job nature present in each industry. Therefore, we hope this paper can provide a deeper understanding on the current Job Satisfaction level of employees, as well as new insights on how personalities may vary across industries and the effects on Job Satisfaction.